PENGUATAN CHARACTER RESILIENCE SPIRITUAL DALAM PENDIDIKAN: PELUANG DAN TANTANGAN DALAM KAJIAN SYSTEMATIC LITERATURE REVIEW - Rahmat Riski; Saifullah Idris (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
ABSTRACT The development of digital technology has brought significant changes to patterns of interaction, learning, and character formation among students. This condition necessitates the strengthening of spiritual character resilience as a foundation for building moral resilience, adaptive abilities, and psychological well-being amid the various challenges of the digital era. This study aims to analyze the development of research related to spiritual character resilience in education and identify the opportunities and challenges of its implementation in the digital era. The study employed a Systematic Literature Review (SLR) approach using data sourced from the Scopus database with the keywords “Character Resilience” AND “Learning Education”. The initial search yielded 87 documents, which were subsequently screened based on publication years (2019–2026), subject areas (Social Sciences, Arts and Humanities, and Multidisciplinary), and open-access article document types. The selection process resulted in 23 articles, but only 16 articles were further analyzed due to their strong relevance to the research focus. The findings indicate that research on spiritual character resilience is dominated by themes such as religious character strengthening, digital resilience, social emotional learning (SEL), integration of local wisdom, and reinforcement of students’ moral identity. The studies also reveal that integrating religious values, local culture, and digital technology provides significant opportunities to enhance moral resilience, emotional regulation, and students’ adaptive abilities. However, challenges such as moral degradation, negative impacts of digital media, low spiritual literacy, and the limited integration of character education into educational curricula remain major obstacles. Therefore, a holistic educational approach involving collaboration among schools, families, communities, and technology based on spiritual values is needed to strengthen students’ spiritual character resilience. ABSTRAK Perkembangan teknologi digital telah membawa perubahan signifikan terhadap pola interaksi, pembelajaran, dan pembentukan karakter peserta didik. Kondisi tersebut menuntut penguatan character resilience spiritual sebagai fondasi untuk membangun ketahanan moral, kemampuan adaptasi, dan kesejahteraan psikologis di tengah berbagai tantangan era digital. Penelitian ini bertujuan untuk menganalisis perkembangan penelitian terkait character resilience spiritual dalam pendidikan serta mengidentifikasi peluang dan tantangan implementasinya pada era digital. Penelitian menggunakan pendekatan Systematic Literature Review (SLR) dengan sumber data berasal dari database Scopus menggunakan kata kunci “Character Resilience” AND “Learning Education”. Hasil pencarian awal memperoleh 87 dokumen, kemudian dilakukan proses penyaringan berdasarkan tahun publikasi 2019–2026, bidang kajian Social Sciences, Arts and Humanities, dan Multidisciplinary, serta jenis dokumen artikel open access. Berdasarkan proses seleksi diperoleh 23 artikel, namun hanya 16 artikel yang dianalisis lebih mendalam karena memiliki keterkaitan paling relevan dengan fokus penelitian. Hasil kajian menunjukkan bahwa penelitian character resilience spiritual didominasi oleh tema penguatan karakter religius, resiliensi digital, social emotional learning (SEL), integrasi budaya lokal, serta penguatan moral dan identitas peserta didik. Penelitian juga menunjukkan bahwa integrasi nilai religius, budaya lokal, dan teknologi digital memiliki peluang besar dalam membangun ketahanan moral, regulasi emosi, dan kemampuan adaptasi peserta didik. Namun demikian, tantangan seperti degradasi moral, dampak negatif media digital, rendahnya literasi spiritual, dan belum optimalnya integrasi pendidikan karakter dalam kurikulum masih menjadi hambatan utama. Oleh karena itu, diperlukan pendekatan pendidikan yang holistik melalui kolaborasi antara sekolah, keluarga, masyarakat, dan teknologi berbasis nilai spiritual.